Phenomenology 2025 Symposium - Costa, Marios (My University, 2026)
I participated in Pheno 2025 (online). The 2025 Phenomenology Symposium (PHENO) held May 19 - 21, 2025 at the University of Pittsburgh. It covered the latest topics in particle phenomenology and theory as well as related issues in astrophysics and cosmology.